Concepts of Nature as Communicative Devices: The Case of Dutch Nature Policy. (1st February 2004) - Keulartz, Jozef; van der Windt, Henny; Swart, Jacques
The recent widespread shift in governance from the state to the market and to civil society, in combination with the simultaneous shift from the national level to supra-national and sub-national levels has led to a significant increase in the numbers of public and private players in nature policy. This in turn has increased the need for a common vocabulary to articulate and communicate views and values concerning nature among various actors acting on different administrative levels. In this article, we will examine the role of concepts of nature as communicative devices in public debates and political decision-making. We try to show that the now dominant functionalist approach to concepts of nature, due to its focus on interests, threatens to narrow public and political communications to purely strategic negotiations. Instead of this functionalist approach we put forward a structuralist approach, which focuses not on interests but on values.